Neuroprotection against CCl4 induced brain damage with crocin in Wistar rats. (17th November 2018) - Altinoz, E; Erdemli, ME; Gul, M; Aksungur, Z; Gul, S; Bag, HG; Kaya, GB; Turkoz, Y
ABSTRACT: Owing to its lipophilic property, carbon tetrachloride (CCl4 ) is rapidly absorbed by both the liver and brain. We investigated the protective effects of crocin against brain damage caused by CCl4 . Fifty rats were divided into five groups of ten: control, corn oil, crocin, CCl4 and CCl4 + crocin. CCl4 administration decreased glutathione (GSH) and total antioxidant status (TAS) levels, and catalase (CAT) activity, while significant increases were observed in malondialdehyde (MDA) and total oxidant status (TOS) levels and superoxide dismutase (SOD) activity. The cerebral cortex nuclear lamina developed a spongy appearance, neuronal degeneration was observed in the hippocampus, and heterochromatic and pyknotic neurons with increased cytoplasmic eosinophilia were observed in the hippocampus after CCl4 treatment. Because crocin exhibits strong antioxidant properties, crocin treatment increased GSH and TAS levels and CAT activities, and decreased MDA and TOS levels and SOD activity; significant improvements also were observed in histologic architecture. We found that crocin administration nearly eliminated CCl4 induced brain damage by preventing oxidative stress.